PREVALENSI INFEKSI SALURAN PERNAPASAN AKUT SEBAGAI PENYEBAB ASMA EKSASERBASI AKUT DI POLIKLINIK PARU RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR BALI TAHUN 2013 - Ni Ketut Suwedarni Yogiswari Putri; Dewa Made Artika (Universitas Udayana, 2017)
Data of WHO in 2013 and Riskesdas in 2007 showed the number of asthmatics increased. Asthma occurs due to the interaction between host and environmental factors. The most-considered environmental factor that caused exacerbation is acute respiratory infection. This research aimed to determine prevalence and types of acute respiratory infection which caused acute asthma exacerbation in Pulmonology Polyclinic General Hospital Sanglah 2013. This research used retrospective descriptive study in design with medical records as data sources. The samples of this research were patient with acute exacerbation asthma in Pulmonology Polyclinic General Hospital Sanglah 2013. From 84 people, acute respiratory infection caused acute asthma exacerbation in 65 people (77.4%). From 65 people, 3 people (4.6%) had rhinitis, 2 people (3.1%) had sinusitis, 8 people (12.3%) had pharyngitis, 23 people (35.4%) had laryngitis, 1 people (1.5%) had tonsillitis, 3 people (4.6%) had bronchitis, and 25 people (38.5%) had pneumonia. Acute respiratory infection was the most common causes of acute asthma exacerbation compared to non infection and the most common type of infection was pneumonia. Keywords: prevalence, acute respiratory infection, acute asthma exacerbatio